Analysis of crude oil and gasoline prices through copulas - Melo e Silva Accioly, Ricardo; Lucena Aiube, Fernando Antonio (Cadernos do IME - Série Estatística, 2008)
In this paper we investigate the dependence of crude oil and gasoline prices. The understanding of the behavior of this dependence is useful for modeling the portfolio of investments in an integrated oil company. An accurate simulation of the behavior of these prices reveals precisely the risk and return of the portfolio. Morover the movements of these prices is crucial for goverment planing since they affect the overall economy of developed and developing countries. The classical approach which uses elliptical distributions to model the risk factors can be misleading since they are actually not elliptical. We used copula to establicsh such dependence since this methodolgy precludes the use of elliptical distributions. We found a change in the behavior of prices in the recent period compared to those in beginning of the decade and this fact is also reported in the literature. This change is observed through different copula models that were adjusted. These results were confirmed with a bootstrap analysis.